A new tribe of tarsonemid mites (Trombidiformes: Heterostigmatina) parasitic on tetrigid grasshoppers (Orthoptera) - Seeman, Owen D.; Lindquist, Evert E.; Husband, Robert W. (Zootaxa, 2018)
Podotarsonemini tribe nov. (Tarsonemidae: Acarapinae), with one nominate genus Podotarsonemus gen. nov., is proposed for seven new species of tarsonemid mites collected from the hindwings of pygmy grasshoppers of the family Tetrigidae (Orthoptera). The new tribe is placed within the tarsonemid subfamily Acarapinae on the basis of several morphological synapomorphies, as well as on parasitism of insects. In light of this new tribe, a revised description of the Acarapinae is provided, as are full tribal, generic and species descriptions for the Podotarsonemini, and a key to species. In view of Podapolipidae, the sister family of Tarsonemidae, consisting entirely of obligatory parasitic mites, the distinction between the two constituent sister families of Tarsonemoidea as well as the ancestral feeding habits of that superfamily are considered. These mites and their host grasshoppers were collected from Bolivia, Ecuador, Honduras, southern India, Japan, Papua New Guinea, South Africa and two localities in north-eastern Australia. This distribution suggests that the Podotarsonemini are an ancient lineage of Tarsonemidae that radiated on the Gondwanan Tetrigidae during the Jurassic.